Healthcare inequities and barriers to access for homeless individuals: a qualitative study in Barcelona (Spain) - Andrés Cernadas; Ángela Fernández (BMC, 2021)
Abstract Background In Spain, homeless individuals have lower perceived quality of health than the rest of the population and their life expectancy is 30 years lower than the national average. While the Spanish health system provides universal access and coverage, homeless individuals do not access or use public care enough to maintain their health. The objective of this study is to determine if homeless individuals can access public health services in conditions of equality with the rest of the population, as established in healthcare legislation, and to better understand the causes of observed inequalities or inequities of access. Methods A detailed qualitative study was carried out in the city of Barcelona (Spain) from October 2019 to February 2020. A total of nine open and in-depth interviews were done with homeless individuals along with seven semi-structured interviews with key informants and two focus groups. One group was composed of eight individuals who were living on the street at the time and the other consisted of eight individuals working in healthcare and social assistance. Results The participants indicated that homeless individuals tend to only access healthcare services when they are seriously ill or have suffered some kind of injury. Once there, they tend to encounter significant barriers that might be 1) administrative; 2) personal, based on belief that that will be poorly attended, discriminated against, or unable to afford treatment; or 3) medical-professional, when health professionals, who understand the lifestyle of this population and their low follow-through with treatments, tend towards minimalist interventions that lack the dedication they would apply to other groups of patients. Conclusions The conclusions derived from this study convey the infrequent use of health services by homeless individuals for reasons attributable to the population itself, to healthcare workers and to the entire healthcare system. Accordingly, to reduce inequities of access to these services, recommendations to healthcare service providers include adapting facilities to provide more adequate care for this population; increasing sensitivity/awareness among healthcare workers; developing in situ care systems in places where the homeless population is most concentrated; and establishing healthcare collaboration agreements with entities that work with this population.